Temperature-sensitive poly(amino-oxime) hydrogel, preparation method and application thereof in uranium adsorption
Patent Information
- Application Number
- CN202310413892.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-18
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-04-18
AI Technical Summary
[0008]有鉴于此,本发明提供了一种温敏性聚偕胺肟水凝胶材料的制备方法,解决了现有同类材料对铀吸附量低且吸附效率低的问题
[0020] It should be noted that this invention is used for the separation and extraction of uranium. Due to the introduction of a temperature-sensitive hydrogel structure, the adsorbent can be used for uranium adsorption in a higher temperature environment, thereby increasing the adsorption rate and adsorption capacity of uranium.
Smart Images

Figure CN116478426B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of novel adsorption materials, and in particular to a method for preparing a thermosensitive poly(ammidine) oxime hydrogel that can be used for uranium adsorption. Background Technology
[0002] Rapid industrialization has led to high energy demand and environmental pollution. Nuclear energy, as one of the main clean energy sources, has become a crucial global strategy, especially in the next decade. Uranium, as a key element in nuclear fuel, is in high demand. Ore uranium reserves are very limited and unevenly distributed, while seawater is rich in uranium resources. Extensive research has been conducted on technologies for extracting uranium from seawater, such as ion exchange flotation, biological treatment, membrane treatment, chemical precipitation, superconducting magnetic separation, and adsorption, among which adsorption is considered the most effective.
[0003] Existing inorganic adsorbents for uranium adsorption (such as lead compounds, manganese dioxide, and basic zinc carbonate) have advantages such as fast adsorption rate and easy recovery and elution, but they also have disadvantages such as poor selectivity for uranium adsorption and small adsorption capacity. Organic adsorbents (such as phosphonic acids and a class of ammonia oxime compounds) have better selectivity and larger adsorption capacity, but due to the polymer properties of single polyammonia oximes, uranyl ions have difficulty diffusing into the material, resulting in low material utilization and resource waste. Ammonia oxime adsorbents are currently recognized as the adsorbents with the strongest coordination adsorption capacity for uranium. Existing reports on ammonia oxime adsorbents generally show uranium adsorption at room temperature, but the reaction rate is low at low temperatures, with adsorption equilibrium times of almost 12 hours or more, resulting in low adsorption efficiency and limiting the practical application of such materials.
[0004] Hydrogels are a type of hydrophilic gel with a three-dimensional network structure. They can swell rapidly in water and retain a large amount of water without dissolving, while maintaining a relatively stable structure and morphology. Some hydrophilic small molecules can diffuse and permeate freely between the three-dimensional network of hydrogels, possessing a diffusion coefficient close to that in aqueous solutions. Therefore, hydrogels are often used to adsorb small molecules, such as heavy metal ions, from aqueous solutions.
[0005] Currently, hydrogel-based uranium adsorbents have attracted increasing attention due to their excellent uranium adsorption performance. However, nitrile-containing polymers with good uranium adsorption performance, such as polyamine oxime adsorbents, are usually insoluble in water. Existing methods require first grafting or copolymerizing nitrile groups to prepare organic gels, and then converting the organic gels into hydrogels. The preparation process is relatively complex, and uranium adsorption is usually carried out at room temperature, resulting in a long adsorption equilibrium time and low adsorption efficiency, which severely limits the uranium adsorption capacity and adsorption rate.
[0006] Therefore, developing hydrogel materials suitable for uranium adsorption and separation at higher temperatures is of great significance. Thermosensitive hydrogels are intelligent hydrogels that undergo morphological changes in response to external temperature variations. They are generally composed of cross-linked polymer chains with a three-dimensional network structure. Due to the large number of hydrophilic and hydrophobic groups on their chains, changes in the strength of the interaction between these two groups when the ambient temperature changes can lead to swelling or shrinkage of the gel structure. When thermosensitive hydrogels are used for metal ion adsorption, at temperatures above the phase transition temperature, the hydrogel shrinks, which can limit the detachment of adsorbed material and ensure a high adsorption capacity. Simultaneously, at higher temperatures, the hydrogel can exhibit a higher adsorption rate and reduce the adsorption equilibrium time.
[0007] In summary, it is essential to develop a thermosensitive poly(amine oxime) hydrogel for the adsorption and separation of uranium ions in liquid-phase systems. Summary of the Invention
[0008] In view of this, the present invention provides a method for preparing a thermosensitive poly(amine oxime) hydrogel material, which solves the problems of low uranium adsorption capacity and low adsorption efficiency of existing similar materials.
[0009] It should be noted that this invention achieves a synergistic effect by combining polyamine oxime and hydrogel. Uranyl ions can travel between the three-dimensional network of the hydrogel, and the ammamine oxime group has high selectivity and high adsorption capacity for uranyl ions. By effectively combining the advantages of both, efficient and highly selective uranium adsorption is achieved.
[0010] Furthermore, this invention combines thermosensitive N-isopropylacrylamide with poly(ammonia) oxime, which has high selectivity and high adsorption capacity, to form a thermosensitive hydrogel. When the ambient temperature of the gel increases, the reaction rate accelerates. Due to changes in the hydrophilic / hydrophobic interaction of the thermosensitive material, the gel structure shrinks upon heating, trapping the adsorbed uranium ions, thereby increasing the adsorption capacity in high-temperature environments and improving adsorption efficiency.
[0011] To achieve the above objectives, the present invention provides the following technical solution:
[0012] The primary technical objective of this invention is to provide a method for preparing a thermosensitive poly(amine oxime) hydrogel, the method specifically comprising the following steps:
[0013] (1) Heat 120 mL of N,N-dimethylformamide to 45 °C and add 0.16 mol of hydroxylamine hydrochloride. After dissolving, add 0.072 mol of Na2CO3 and 0.048 mol of NaOH. Add 0.16 mol of polyacrylonitrile to the above reaction system. After the polyacrylonitrile is completely dissolved, stir the reaction at 60 °C for 24 h.
[0014] (2) Add 0.036 mol Na2CO3 and 0.024 mol NaOH to the reaction system, stir at 65°C for 12 h; separate the reaction product with deionized water and dry it under vacuum at 60°C to obtain poly(amine oxime) PAO;
[0015] (3) Dissolve 0.5 g of poly(azoamine oxime) PAO in 100 mL of 0.8% NaOH solution, add 2.5 g of thermosensitive monomer N-isopropylacrylamide, 4.0 g of initiator 2,2'-azo(2-methylpropylimidazolium) dihydrochloride, 0.31 g of crosslinking agent N,N-methylenebisacrylamide BIS, and 1 mL of 1 mg / mL UO2. 2+ The ionic solution was reacted at 30°C for 3 hours, 40°C for 1 hour, 50°C for 1 hour, 60°C for 1 hour, and 70°C for 3 hours. After rinsing three times with deionized water, the thermosensitive poly(amine oxime) hydrogel PAOU was obtained.
[0016] It is worth noting that in step (1), hydroxylamine hydrochloride reacts with sodium hydroxide to generate hydroxylamine, and in an alkaline environment, hydroxylamine undergoes an addition reaction with polyacrylonitrile to generate a methylamine oxime; in step (2), N,N-dimethylformamide reacts with sodium hydroxide to generate formate and dimethylamine; and formate and dimethylamine are both readily soluble in water, so the final product obtained after adding alkali is a methylamine oxime after separation with deionized water.
[0017] The second technical objective of this invention is to provide a thermosensitive poly(ammoxime) hydrogel prepared by the above method.
[0018] The third technical objective of this invention is to provide the application of the thermosensitive poly(ammoxime) hydrogel prepared by the above method in uranium adsorption.
[0019] It should be noted that the poly(ammoxime) and hydrogel combine to form a three-dimensional network, allowing uranyl ions to rapidly traverse within this network. When the external temperature exceeds the phase transition temperature, the hydrogel shrinks, accelerating the reaction rate. The C=O and =N-OH bonds of the ammoxime group and the C=O bond of N-isopropylacrylamide interact with UO2. 2+ Covalent bonds are formed, achieving synergistic adsorption between the two, thus realizing efficient and highly selective uranium adsorption. Figure 2 ).
[0020] It should be noted that this invention is used for the separation and extraction of uranium. Due to the introduction of a temperature-sensitive hydrogel structure, the adsorbent can be used for uranium adsorption in a higher temperature environment, thereby increasing the adsorption rate and adsorption capacity of uranium.
[0021] As can be seen from the above technical solutions, compared with the prior art, the thermosensitive poly(amine) oxime hydrogel and its preparation method provided by the present invention, and their application in uranium adsorption, have the following superior effects:
[0022] This invention combines poly(ammoxime) with a thermosensitive hydrogel, overcoming the shortcomings of single-substance adsorption. On the one hand, it solves the problem that the uranyl ion is difficult to penetrate the interior of poly(ammoxime) due to the polymer properties, resulting in low material utilization and low adsorption capacity. On the other hand, by combining thermosensitive N-isopropylacrylamide with poly(ammoxime) which has high selectivity and high adsorption capacity to form a thermosensitive hydrogel, the reaction rate is accelerated when the ambient temperature of the gel increases. Due to the change in the strength of the hydrophilic and hydrophobic interactions of the thermosensitive material, the gel structure shrinks when heated, trapping the adsorbed uranium ions, thereby increasing the adsorption capacity in high-temperature environments and improving adsorption efficiency. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0024] Figure 1 (a) is a schematic diagram of the PAOU preparation process, and (b) is a diagram of PAOU adsorbing UO2. 2+ Mechanism diagram.
[0025] Figure 2 A schematic diagram of the structure of PAOU and its relationship with UO2. 2+ Mechanism of action diagram.
[0026] Figure 3 (a)-(e) are DSC charts for PAOU-1 to PAOU-5. Figure 3 (f) is the phase transition temperature diagram of PAOU under the optimal conditions of the present invention for five cycles.
[0027] Figure 4 Infrared spectra of PAN, PAO, NIPAM, and PAOU.
[0028] Figure 5 SEM images of (a) PAOU surface, (b) PAOU cross section, (c) PAOU (uranium-containing) surface, and (d) PAOU (uranium-containing) cross section.
[0029] Figure 6 (a) is the O1s XPS spectrum of PAOU before and after uranium adsorption, (b) is the N1s XPS spectrum of PAOU before and after uranium adsorption, (c) is the XPS spectrum of PAOU before and after uranium adsorption, and (d) is the U4f XPS spectrum of PAOU before and after uranium adsorption.
[0030] Figure 7The graph shows the effect of different temperatures (a), times (b), pH (c), and uranium concentrations (d) on the adsorption capacity of PAOU.
[0031] Figure 8 The selective adsorption diagram of PAOU in a 0.5 mg / g mixed metal ion solution is shown.
[0032] Figure 9 This is a diagram showing five adsorption-desorption cycles of PAOU at 25℃ and 50℃.
[0033] Figure 10 This is a flowchart of PAOU's real seawater adsorption process.
[0034] Figure 11 This is a graph showing the adsorption capacity of PAOU in a real seawater simulation. Detailed Implementation
[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] This invention discloses a method for preparing a thermosensitive poly(ammidine) oxime hydrogel.
[0037] To better understand the present invention, the following embodiments are provided for further detailed description of the present invention, but they should not be construed as limiting the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above-described invention are also considered to fall within the protection scope of the present invention.
[0038] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0039] Example 1
[0040] A method for preparing thermosensitive poly(amine oxime) hydrogel includes the following steps:
[0041] (1) Heat 120 mL of N,N-dimethylformamide to 45 °C and add 0.16 mol of hydroxylamine hydrochloride. After dissolving, add 0.072 mol of Na2CO3 and 0.048 mol of NaOH. Add 0.16 mol of polyacrylonitrile to the above reaction system. After the polyacrylonitrile is completely dissolved, stir the reaction at 60 °C for 24 h.
[0042] (2) Add 0.036 mol Na2CO3 and 0.024 mol NaOH to the reaction system, stir at 60°C for 12 h; separate the reaction product with deionized water and dry it under vacuum at 60°C to obtain poly(amine oxime) (PAO).
[0043] (3) Disperse 0.5 g of poly(aminoamine oxime) (PAO) in 100 mL of 0.5% NaOH solution, add 3.0 g of thermosensitive monomer N-isopropylacrylamide, 4.0 g of initiator 2,2'-azo(2-methylpropylimidazolium) dihydrochloride (AIBA), 0.31 g of crosslinking agent N,N-methylenebisacrylamide (BIS), and 1 mL of 1 mg / mL UO2. 2+ After reacting with ionic solution at 30°C for 3 hours, 40°C for 1 hour, 50°C for 1 hour, 60°C for 1 hour, and 70°C for 3 hours, the solution was washed three times with deionized water to obtain thermosensitive poly(amine oxime) hydrogel (PAOU-3).
[0044] Example 2
[0045] A method for preparing thermosensitive poly(amine oxime) hydrogel includes the following steps:
[0046] (1) Heat 120 mL of N,N-dimethylformamide to 45 °C and add 0.16 mol of hydroxylamine hydrochloride. After dissolving, add 0.072 mol of Na2CO3 and 0.048 mol of NaOH. Add 0.16 mol of polyacrylonitrile to the above reaction system. After the polyacrylonitrile is completely dissolved, stir the reaction at 65 °C for 24 h.
[0047] (2) Add 0.036 mol Na2CO3 and 0.024 mol NaOH to the reaction system, stir at 65°C for 24 h; separate the reaction product with deionized water and dry it under vacuum at 60°C to obtain poly(amine oxime) (PAO).
[0048] (3) Disperse 0.5 g of poly(aminoamine oxime) (PAO) in 100 mL of 0.5% NaOH solution, add 2.5 g of thermosensitive monomer N-isopropylacrylamide, 5.0 g of initiator 2,2'-azo(2-methylpropylimidazolium) dihydrochloride (AIBA), 0.31 g of crosslinking agent N,N-methylenebisacrylamide (BIS), and 1 mL of 1 mg / mL UO2. 2+ After reacting with ionic solution at 30°C for 3 hours, 40°C for 1 hour, 50°C for 1 hour, 60°C for 1 hour, and 70°C for 3 hours, the solution was washed three times with deionized water to obtain thermosensitive poly(amine oxime) hydrogel (PAOU-5).
[0049] Example 3
[0050] A method for preparing thermosensitive poly(amine oxime) hydrogel includes the following steps:
[0051] (1) Heat 120 mL of N,N-dimethylformamide to 45 °C and add 0.16 mol of hydroxylamine hydrochloride. After dissolving, add 0.072 mol of Na2CO3 and 0.048 mol of NaOH. Add 0.16 mol of polyacrylonitrile to the above reaction system. After the polyacrylonitrile is completely dissolved, stir the reaction at 65 °C for 24 h.
[0052] (2) Add 0.036 mol Na2CO3 and 0.024 mol NaOH to the reaction system, stir at 65°C for 12 h; separate the reaction product with deionized water and dry it under vacuum at 60°C to obtain poly(amine oxime) (PAO).
[0053] (3) Disperse 0.5g of poly(aminoamine oxime) (PAO) in 100mL of 0.5% NaOH solution, add 2.5g of thermosensitive monomer N-isopropylacrylamide, 4.5g of initiator 2,2'-azo(2-methylpropylimidazolium) dihydrochloride (AIBA), 0.31g of crosslinking agent N,N-methylenebisacrylamide (BIS), and 1mL of 1mg / mL UO2. 2+ After reacting with ionic solution at 30°C for 3 hours, 40°C for 1 hour, 50°C for 1 hour, 60°C for 1 hour, and 70°C for 3 hours, the thermosensitive poly(amine oxime) hydrogel (PAOU-4) was obtained by rinsing three times with deionized water.
[0054] To further illustrate the superiority of this patented technology over existing technologies, the inventors conducted the following experiments, the details of which are as follows:
[0055] Experiment 1: Used to illustrate the thermosensitivity of PAOU
[0056] The temperature sensitivity of PAOU material (wet weight: approximately 25 mg) was tested using a differential scanning calorimeter (DSC). Instrument parameters were set as follows: N2 protection (flow rate: 50 mL / min), initial temperature 10℃, heated to 90℃ at a rate of 10 K / min, then cooled back to 10℃. An aluminum crucible was used as the sample cell, with dimensions of [missing information].
[0057] Ingredient list for different proportions of PAO / NIPAM / AIBA
[0058]
[0059] For PAOU, by Figure 3As shown in (a)-(c), when the amount of NIPAM is 2.0g and 3.0g, the endothermic and exothermic peaks become less obvious, and the phase transition temperature of the gel is not clear. Therefore, it can be concluded that the amount of NIPAM is better when it is 2.5g.
[0060] Regarding AIBA usage, a comparison Figure 3 As shown in (b), (d) and (e), when the amount of AIBA is 4.5g and 5.0g, the endothermic curve becomes more complex and the number of endothermic peaks increases, which is not conducive to the subsequent exploration of adsorption conditions. Therefore, the amount of AIBA is better when it is 4.0g.
[0061] Experiment 2: To illustrate the structure of PAOU
[0062] Fourier transform infrared spectroscopy was used to analyze the infrared spectra of PAO, NIPAM, and freeze-dried PAOU using the KBr pellet method. Field emission scanning electron microscopy was used to analyze the surface and cross-section microstructure of freeze-dried PAOU and PAOU (containing uranium). X-ray spectroscopy was used to analyze the freeze-dried PAOU and PAOU (containing uranium).
[0063] Figure 4 1637 cm of the amine oxime group -1 (C=N) and 945cm -1 (NO) Specific main peak and NIPAM's 3294cm -1 (NH), 1653cm -1 The (-C=O) stretching vibration peak indicates that PAO has been cross-linked with NIPAM in the hydrogel.
[0064] like Figure 5 In the SEM images, the hydrogel exhibits a relatively large, uniform microporous structure before uranium absorption. Figure 5 (a, b)) After adsorption, the interior no longer has a large number of pores, and the pores are significantly reduced in size. Figure 5 (c, d)). This indicates that the thermosensitive monomer NIPAM was successfully polymerized with PAO, and also demonstrates that the microstructure of the gel can be significantly modulated by changing the temperature.
[0065] like Figure 6 XPS spectra showed that the specific biphasic peaks (392.7 eV, 381.9 eV) in the uranium-adsorbed hydrogel and the uranium-containing hydrogel compared to the original PAOU hydrogel indicated that uranyl ions had been adsorbed in the hydrogel.
[0066] Experiment 3: To illustrate the adsorption performance of PAOU
[0067] UO2 2+Concentration was determined using the arsene III ultraviolet spectrophotometric method, with the detection wavelength set at 652 nm. The standard curve testing procedure is as follows:
[0068] UO2 was prepared at concentrations of 20, 40, 60, 80, and 100 μg / mL, respectively. 2+ Take 1 mL of each solution and add it to a 10 mL volumetric flask. Then, add 0.5 mL of 0.1 mol / L hydrochloric acid, 1 mL of 0.05 mol / L Na₂EDTA solution, and 1 mL of 500 mg / L azoarsine III solution sequentially. Dilute to the mark with ultrapure water to prepare standard solutions with concentration gradients of 2 μg / mL, 4 μg / mL, 6 μg / mL, 8 μg / mL, and 10 μg / mL. Calculate the uranium concentration using a linear regression equation derived from the standard curve.
[0069] Determination of optimal adsorption temperature: 10 mg of thermosensitive poly(amine oxime) hydrogel was placed in 80 mL of 50 μg / mL UO2 solution with pH = 4.52. 2+ The solution was placed in a constant temperature water bath shaker and adsorbed for 1 hour at different temperatures (45℃, 50℃, 55℃, 60℃, 65℃, 70℃), then filtered. The residual UO2 in the filtrate was measured. 2+ To determine the optimal adsorption temperature based on the concentration of the target material. Figure 7 (a)).
[0070] Determination of optimal adsorption time: 10 mg of thermosensitive poly(amine oxime) hydrogel was placed in 80 mL of 50 μg / mL UO2 solution with pH = 4.52. 2+ The solution was placed in a constant temperature water bath shaker at 50℃ for adsorption at 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 120 min, and 180 min, respectively, and then filtered. The residual UO2 in the filtrate was measured. 2+ To determine the optimal adsorption temperature based on the concentration of the target material. Figure 7 (b)).
[0071] Determination of optimal adsorption pH: 10 mg of thermosensitive poly(amine oxime) hydrogel was placed in 80 mL of 50 μg / mL UO2. 2+ In the solution, the pH was adjusted to 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, and 7.0. The solutions were then placed in a 50°C constant-temperature water bath shaker for 50 minutes for adsorption, followed by filtration. The remaining UO2 in the filtrate was measured. 2+ To determine the optimal adsorption pH, the concentration of the target pH is determined. Figure 7 (c)).
[0072] Determination of optimal adsorption concentration: Hydrogels containing 10 mg of thermosensitive poly(amine oxime) were placed in 80 mL of solutions containing 0.10 mg / mL, 0.20 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, and 0.9 mg / mL L / O2, respectively. 2+ In the solution, the pH was adjusted to 4.5, and the solution was placed in a constant temperature water bath shaker at 50℃ for 50 minutes for adsorption. After filtration, the residual UO2 in the filtrate was measured. 2+ To determine the optimal adsorption concentration, the concentration of the adsorption concentration is determined. Figure 7 (d)).
[0073] The uranium adsorption content of the adsorbent is obtained according to the following formula (1):
[0074]
[0075] Where Q is the adsorption amount, C0 is the original concentration of the uranium solution, and C t The concentration of the filtrate after uranium adsorption, where V is the volume of the uranium solution.
[0076] Experiment 4: To illustrate the cyclic adsorption performance of PAOU at room temperature (25℃) and high temperature (50℃).
[0077] Two groups of 10 mg thermosensitive poly(ethylene glycol) oxime hydrogels were placed in 80 mL of 0.5 mg / mL UO2 solution. 2+ In the solution, the pH was adjusted to 4.0, and the solution was placed in a constant temperature water bath shaker at room temperature (25℃) (PAOU-L) and 50℃ (PAOU-H) for 50 min for adsorption, respectively, and then filtered. The residual UO2 in the filtrate was measured. 2+ To determine the concentration of uranium, the uranium-adsorbed hydrogel membrane was immersed in 400 mL of eluent (1 mol / L Na₂CO₃ and 0.1 mol / L H₂O₂) and magnetically stirred for 60 min. After elution, the hydrogel was removed from the eluent and immersed in pure water, with the water changed several times. Finally, the hydrogel was immersed in a solution containing uranium for the next cycle. This adsorption-elution process was repeated five times.
[0078] Depend on Figure 8The initial uranium adsorption capacity of the PAOU high-temperature cycled hydrogel (PAOU-H) was 704.32 mg / g, while that of the room-temperature cycled hydrogel (PAOU-L) was 435.36 mg / g. After 5 adsorption-desorption cycles, the high-temperature cycled hydrogel retained 82.24% of its original uranium adsorption capacity, and the uranium elution efficiency remained at 86.63%. The room-temperature cycled hydrogel retained 81.73% of its original uranium adsorption capacity, with an initial adsorption capacity only 62.20% of that of the high-temperature cycled hydrogel, but the elution efficiency remained at 86.57%, close to that of the high-temperature cycled hydrogel. These results indicate that this hydrogel possesses rapid and efficient uranium adsorption-desorption capabilities, and the material exhibits good adsorption performance at high temperatures, thus allowing for repeated use to extract uranium. Experiment 5: Used to illustrate the selective adsorption performance of PAOU.
[0079] Take 10 mg of PAOU (dry weight) and add it to 80 mL of a 0.6 mg / mL mixed metal ion solution (Cu) at pH 4.0. 2+ Mg 2+ Ca 2+ Pb 2+ Cd 2+ Na + K + Zn 2+ UO2 2+ The adsorption was carried out at 50℃ for 1 hour. The adsorption of each metal ion was measured by ICP-Mass. By analyzing the concentrations before and after adsorption, the adsorption results for different ions could be calculated. The results are as follows: Figure 9 As shown, the hydrogel's adsorption capacity for uranium is far greater than that of any other metal ion, indicating that the hydrogel of this invention has the potential application value of extracting large quantities of uranium from seawater.
[0080] Experiment 6: To illustrate the adsorption performance of PAOU in real seawater.
[0081] like Figure 10 As shown, 0.05 g (dry weight) of adsorbent was packed into the adsorption column of the seawater circulating adsorption system, and the seawater flow rate was controlled at 15 mL / min using a pump. The uranium extraction capacity of the adsorbent was tested in 40 L of natural seawater at 50 °C. The 40 L of natural seawater came from the South China Sea. The natural seawater was filtered through a 0.45 μm sterile filter to remove impurities such as marine bacteria and algae, eliminating the influence of marine organisms on uranium extraction. For two days, 5 mL of circulating adsorbed seawater was sampled every 12 hours, and the concentration of the adsorbed seawater was measured using a UV spectrophotometer to calculate the PAOU adsorption capacity. The results are shown below. Figure 11 As shown, after adsorption in natural seawater for 2 days, the uranium extraction capacity of the adsorbent PAOU reached 0.502 mg / g.
[0082] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a thermosensitive poly(amine oxime) hydrogel, characterized in that, The method specifically includes the following steps: (1) Mix N,N-dimethylformamide with hydroxylamine hydrochloride, then add Na2CO3 and NaOH to adjust the pH, and add polyacrylonitrile to the above reaction system and stir to react; (2) Add Na2CO3 and NaOH to the reaction system to adjust the pH value and continue the reaction; separate and dry the reaction product to obtain poly(amine oxime) PAO; (3) The poly(amine oxime) PAO was dispersed in NaOH solution, and N-isopropylacrylamide, 2,2'-azo(2-methylpropylimidazolium) dihydrochloride, N,N-methylenebisacrylamide and UO2 were added. 2+ The ionic solution is subjected to a gradient heating reaction. After the reaction is completed, it is rinsed and filtered to obtain the thermosensitive poly(amine oxime) hydrogel PAOU.
2. The method for preparing a thermosensitive poly(amine oxime) hydrogel according to claim 1, characterized in that, In step (1), the molar ratio of Na2CO3 to NaOH is 3:2-4, the molar ratio of hydroxylamine hydrochloride to polyacrylonitrile is 1:1-1.5, the molar ratio of polyacrylonitrile to N,N-dimethylformamide is 4:3-5, the reaction temperature is 60℃-70℃, and the reaction time is 24h.
3. The method for preparing a thermosensitive poly(ethylenediamine oxime) hydrogel according to claim 1, characterized in that, In step (2), the molar ratio of Na2CO3 to NaOH is 3:2-4, the pH value is adjusted to 8-10, the reaction time is 12-24h, and the reaction temperature is 60-70℃.
4. The method for preparing a thermosensitive poly(ethylenediamine oxime) hydrogel according to claim 1, characterized in that, In step (3), the mass ratio of poly(azo(2-methylpropyl)acrylamide) to N-isopropylacrylamide is 1:5-6; the mass ratio of poly(azo(2-methylpropylimidazolium))dihydrochloride is 1:8-10; the mass ratio of poly(azo(2-methylpropylimidazolium))dihydrochloride is 1:1.6-2; the gradient temperature increase reaction is performed as follows: React at 30℃ for 3 hours, at 40℃ for 1 hour, at 50℃ for 1 hour, at 60℃ for 1 hour, and at 70℃ for 3 hours.
5. A thermosensitive poly(ammoxime) hydrogel prepared by the method described in claim 1.
6. The application of a thermosensitive amine oxime hydrogel prepared by the method of claim 1 or the thermosensitive amine oxime hydrogel of claim 5 in uranium adsorption.